Competitive Coordination‐Pairing between Ru Clusters and Single‐Atoms for Efficient Hydrogen Evolution Reaction in Alkaline Seawater. Issue 40 (1st September 2022) - Qian, Chunzhu; Shao, Wenqian; Zhang, Xingyue; Mu, Xueqin; Gu, Xiangyao; Yu, Min; Ma, Ligang; Liu, Suli; Mu, Shichun
Abstract: The coordination environment of Ru centers determines their catalytic performance, however, much less attention is focused on cluster‐induced charge transfer in a Ru single‐atom system. Herein, by density functional theory (DFT) calculations, a competitive coordination‐pairing between Ru clusters (RuRu bond) and single‐atoms (RuO bond) is revealed leading to the charge redistribution between Ru and O atoms in ZnFe2 O4 units which share more free electrons to participate in the hydrogen desorption process, optimizing the proton adsorption and hydrogen desorption. Thus, a clicking confinement strategy for building a competitive coordination‐pairing between Ru clusters and single‐atoms anchored on ZnFe2 O x nanosheets over carbon via RuO ligand (Ru1, n ‐ZnFe2 O x ‐C) is proposed. Benefiting from the optimized coordination effect and the electronic synergy between Ru clusters and single‐atoms, such a catalyst demonstrates the excellent activity and excellent stability in alkaline and seawater media, which has exceptional hydrogen evolution reaction activity with overpotentials as low as 10.1 and 15.9 mV to reach the current density of 10 mA cm −2 in alkaline and seawater media, respectively, higher than that of commercial Pt/C catalysts as a benchmark. Furthermore, it owns remarkably outstanding mass activity, approximately 2 and 8 times higher than that of Pt catalysts in alkaline and seawater media, respectively. Abstract : A clicking confinement strategy is employed to build a competitive coordination‐pairing between Ru clusters and single‐atoms anchored on ZnFe2 O x nanosheets over carbon via RuO ligand (Ru1, n ‐ZnFe2 O x ‐C), which demonstrates the excellent activity and excellent stability in both alkaline and seawater media, higher than that of commercial Pt catalysts as a benchmark.